Alternatives to Black‐76 Model for Options Valuations of Futures Contracts. Issue 114 (22nd July 2021) - Swishchuk, Anatoliy; Roldan‐Contreras, Ana; Soufiani, Elham; Martinez, Guillermo; Selfi, Mohsen; Agrawal, Nishant; Yao, Yao
Abstract : In this paper, we propose some alternatives to the Black‐76 model to the value European options on figures contracts in which the underlying market prices can be negative or/and mean‐reverting. We specifically consider two models, namely Ornstein‐Uhlenbck (OU), for negative prices, and continuous‐time GARCH (or inhomogeneous geometric Brownian motion), for positive prices. We then analyze the results and compare them with Black‐76, the most commonly used model, when the underlying market prices are positive. Numerical examples are presented using WTI and NYMEX NG datasets.